(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The study concerns the influence of various variants of severe plastic deformation in the Equal Channel Angular Pressing (ECAP) process on the microstructure, microhardness and conductivity of the CuCoNi alloy. The evolution of the microstructure was investigated by microscopic observations and back-scattered electron diffraction (EBSD) in a scanning electron microscope (SEM). Using the Vickers method, tests of microhardness of samples were performed after various variants of the ECAP process. The conductivity was measured with an eddy current device for measuring electrical conductivity based on the complex impedance of the measuring probe. The results indicated the possibility of deformation of CuCoNi alloys in the process of pressing through the ECAP angular channel and developing their microstructure and properties. The method is an effective tool for strengthening the tested copper alloy by refinement of the microstructure. After the first pass, the grain size was reduced by 80%. Increasing the plastic deformation temperature did not significantly affect the obtained level of microstructure fragmentation - the average grain size is approx. 1.4-1.5 μm. The fragmentation of the microstructure had a negligible effect on the conductivity of the CuCoNi alloy, which after the ECAP process oscillated at the value of 13 MS/m.